Retained avidity despite reduced cross-binding and cross-neutralizing antibody levels to Omicron after SARS-COV-2 wild-type infection or mRNA double vaccination - Harthaller, Teresa; Falkensammer, Barbara; Bante, David; Huber, Maria; Schmitt, Melanie; Benainouna, Habib; Rössler, Annika; Fleischer, Verena; von Laer, Dorothee; Kimpel, Janine; Würzner, Reinhard; Borena, Wegene (Frontiers in Immunology, 2023)
The rapid evolution of SARS-CoV-2 has posed a challenge to long lasting immunity against the novel virus. Apart from neutralizing function, binding antibodies induced by vaccination or infection play an important role in containing the infection. To determine the proportion of wildtype (WT)-generated antibodies recognizant of more recent variants, plasma samples from either SARS-CoV-2 WT infected (n=336) or double-mRNA (Comirnaty) vaccinated individuals (n=354, age and sex matched to the convalescent group) were analyzed for binding-antibody capacity against the S1 protein of the BA.1 omicron variant. Overall, 38.59% (95% CI: 37.01-40.20) of WT-generated antibodies recognized omicron BA.1 S1 protein (28.83%, 95% CI: 26.73-30.91 post-infection and 43.46%, 95% CI: 41.61-45.31 post vaccination, p<0.001). While the proportion of WT-generated binding and neutralizing-antibodies also binding to BA.1 is substantially reduced, avidity of the remaining antibodies against the omicron variant was non-inferior to that of the ancestral virus. With avidity to omicron : 39.7% (95% CI: 38.1–41.3) as compared to the avidity to WT : 27.0% (95% CI: 25.5-28.4), respectively (p<0.001) our results suggest that an aspect of functional immunity against the novel strains was considerably retained after WT contact, speculatively counteracting the impact of immune evasion towards neutralization of the strain. Further, we noticed a modestly – yet statistically significant – higher avidity towards the omicron epitopes among the vaccinated group (42.2%; 95% CI: 40.51-43.94) as compared to the convalescent counterparts (36.4%; 95% CI: 33.42-38.76) (p=0.003), even after adjusting for antibody concentration, suggesting an advantage of repeated exposure in generating robust immunity.